IMPLEMENTASI METODE PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN AKTIVITAS BELAJAR PADA MATA PELAJARAN IPS - Handayani Harahap; Ponidi Ponidi (STKIP Singkawang, 2024)
This study aims to find out the implementation of problem-based learning methods to improve learning activities in social studies subjects in class V SD Negeri 101740 Simangambat Kec. Simangambat Kab. Paluta. The research approach used in this study uses qualitative methods, this research was conducted at SD Negeri 101740 Simangambat precisely in class V which is located in Kec. Simangambat, Kab. Padang Lawas Utara, in this study the data was collected by observation, interview and documentation methods. Data sources in this study were taken from teachers and students, The data analysis technique used in this study is the Miles & Huberman method, which consists of data collection, data reduction and data presentation. The results of this study are the learning process of social studies subjects in class V at SD Negeri 101740 Simangambat using methods that are quite varied by collaborating the lecture method with problem-based learning methods, the application of problem-based learning methods (PBM) in social studies subjects at SD Negeri 101740 Simangambat can be concluded that the application of these methods runs effectively and the challenges faced by teachers when applying problem-based learning methods in social studies subjects at SD Negeri 101740 Simangambat the main obstacle lies in the complex process of group division and group presentations which result in a lot of time consuming.